Betting high, feeling low: a cross-sectional examination of gambling severity and psychological distress among Ghanaian youth - Emmanuel Manu; Francis Acquah; Mbuyiselo Douglas; Emmanuel Akitty; Emefa Priscilla Zanu; Mary Akua Ampomah; Prince Owusu Adoma (BMC Public Health, 2024)
Abstract Background Little is known about the nexus between online gambling and psychological distress among youth, especially in Ghana. This study aimed to investigate the effects of online sports betting on psychological distress, focusing on depression, anxiety, and stress among young individuals in the Volta region of Ghana. Methods A cross-sectional study was carried out at various betting centers in the Volta region of Ghana. Four hundred and three (403) participants were selected using a multi-stage sampling method. The study used a standardized questionnaire to assess psychological distress with the Depression, Anxiety, and Stress Scale (DASS 21) and problematic gambling with the Problem Gambling Severity Index (PGSI). The analysis included both descriptive and inferential methods. These include the implementation of the bootstrap technique within multiple regression models using the current versions of Jeffreys’s Amazing Statistics Program (JASP) [0.18.2], Statistical Package for the Social Sciences (SPSS) [29.0.2], and Microsoft Excel (2019). Results The study found a prevalence of 40% for problematic gambling and 44% for moderate gambling problems among participants, resulting in an overall gambling prevalence of 84%. Regarding psychological distress, the estimated prevalence of depression among participants was 43.6%, with stress reported at 31.1% and anxiety at 68.8%. The overall prevalence of psychological distress was 48%. When analyzing the link between gambling and psychological distress, the study noted that males were more prone to gambling-related psychological distress than females (β = 2.036, p = 0.025). Furthermore, individuals with problem gambling showed the highest probability of experiencing more significant psychological distress compared to other groups (β = 9.228, p = 0.002), followed by those with moderate gambling levels (β = 3.283, p = 0.002). Conclusion We recommend that the mental health unit of the Ghana Health Service, in collaboration with the Gaming Commission of Ghana, should develop youth-friendly interventions to address the prevalence and onset of problematic gambling among the youth, especially males. This could, in turn, reduce the prevalence of psychological distress among youth engaged in online gambling in Ghana.